1980
DOI: 10.1073/pnas.77.5.2757
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of fetal hemoglobin synthesis decreases during erythroid cell maturation.

Abstract: Peripheral blood mononuclear cells from pregnant and postpartum women were cultured in vitro with erythropoietin. Burst-forming unit (BFU-E)derived erythroid colonies composed of immature erythroblasts with low hemoglobin contents were observed by day 8 of culture. By day 12 of culture, numerous BFU-E-derived erythroid colonies with high hemoglobin contents were present. The Y/(y + f) globin synthetic ratio was approximately 12% in the early cultures and 6% in the late cultures, indicating that the proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 23 publications
3
13
0
1
Order By: Relevance
“…Several previous studies have shown that Epo, apart from implementing the terminal maturation program, produces differences in the globin species formed (23)(24)(25)(26)(27)(28)(29). These changes, like those reported here for B6SUtA cells, could be effected by Epo in any one of several different direct or indirect ways.…”
Section: Discussionsupporting
confidence: 45%
“…Several previous studies have shown that Epo, apart from implementing the terminal maturation program, produces differences in the globin species formed (23)(24)(25)(26)(27)(28)(29). These changes, like those reported here for B6SUtA cells, could be effected by Epo in any one of several different direct or indirect ways.…”
Section: Discussionsupporting
confidence: 45%
“…100 000 cells increased by the peak day, the relative frequency between groups remained similar. The number of colonies/ 100 000 cells previously reported for fetal (7)(8)(9), newborn (3,5,6,8,13,17,(20)(21)(22)(23), and adult (5,6,8,12,18,20,(24)(25)(26)(27) blood cultures were 40-500,9-220, and 2-256, respectively. Our values fall within the ranges reported by others.…”
Section: Fetal Newborn Adultmentioning
confidence: 99%
“…Hematological parameters were determined by standard laboratory procedures, using a Coulter S electronic counter. Hemoglobin studies, including starch gel electrophoresis, determinations of Hb A2 by microcolumn chromatography (normal range 1.8-3.3%) and Hb F by the Betke method (normal range 0.4-1.2%), were done as previously described (7). Hb H inclusion bodies in peripheral blood erythrocytes were carefully searched for under a light microscope, after the blood was incubated with brilliant cresyl blue (British Drug House) for 2 hr at 37°C (8).…”
Section: Methodsmentioning
confidence: 99%